On Their Mark Rambert's first season with Mark Baldwin reviewed - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Review of Rambert's first season with Mark Baldwin. PALABRAS CLAVE: Rambert, Mark Baldwin, Javier De Frutos's Elsa Canasta, Karole Armitage's Living Toys.